Review on Histopathological Techniques in Cervical Cancer Screening - Gamde, Matthias Solomon; Adeleye, Temitope Mary; O Adisa, James (Asian Pacific Journal of Cancer Care, 2024)
Histopathological techniques remain the basis for cervical cancer care by making diagnosis and model treatment options to improve patient outcomes. It involves the examination of cervical tissue samples to establish a diagnosis, grade precancerous lesions, and stage invasive cancer that guide treatment options. We examined published reports and provided updated information on histopathological techniques in cervical cancer screening using the PRISMA guidelines for review. Histopathology examination is used to confirm precancerous lesions and stage invasive cancer. Accumulated data obtained also informs healthcare providers about the severity of the lesions, allowing decisions for personalized treatment plans and prognosis. While cytology screening is an important tool for cervical cancer screening, histopathological techniques are indispensable to confirm the diagnosis and determine appropriate treatments. Therefore, it is essential to continue streamlining the techniques and scoring patterns to guarantee for their reliability in various contexts.